Immatures of Nesticodes rufipes (Araneae, Theridiidae) Causing Considerable Damage to Ant Colonies in the Laboratory - Fox, Eduardo Gonçalves Paterson [UNESP]; Brescovit, Antonio Domingos; Solis, Daniel Russ [UNESP]; De Jesus, Carlos Massuretti [UNESP]; Bueno, Odair Correa [UNESP] (My University, 2009)
Here we report the frequent occurrence of Nesticodes rufipes (Lucas) (Araneae; Theridiidae) immature spiders inside laboratory colonies of various ant species. It was the only spider species frequently found to invade the ant colonies in our laboratory. The spiders were capable of killing ant workers of different sizes and were even able to kill queens, and were not always easy to spot. This occurrence adds to the body of knowledge about this species, and may be useful to others trying to rear ant colonies in the laboratory.
Keywords: Ants; Insect rearing; Spiders